Are sound dogs mechanically symmetric at trot? - Colborne, G. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
A two-year-old, sound Labrador Retriever was determined to be ’right hind limb dominant’ by comparison of total hind limb moments of support using inverse dynamics. Net joint moments at the hip, tarsal and metatarsophalangeal joints were larger on the right side. Vertical joint reaction forces at the stifle were larger on the right, and horizontal stifle joint reaction forces were smaller on the right. The crus segment was more cranially inclined on the right side through most of stance, but the angle of the resultant stifle joint reaction force vector against the long axis of the crus segment was identical between the right and left sides. The cranially inclined crus segment orientation on one side, coupled with the larger vertical joint reaction force, may result in an internal asymmetry in stifle joint mechanics, although the effects of this on cruciate ligament stresses remain to be determined.
Keywords: Canine; gait; kinetics; kinematics; symmetry